Impact of body mass index on outcomes in European patients with atrial fibrillation: the ESC EHRA EORP Atrial Fibrillation General Long-Term registry (AFGen LT). (25th November 2020) - Boriani, G; Proietti, M; Laroche, C; Fauchier, L; Marin, F; Nabauer, M; Potpara, T; Dan, G.A; Kalarus, Z; Tavazzi, L; Maggioni, A.P; Lip, G.Y.H
Abstract: Introduction: The impact of body mass index (BMI) on outcomes in patients with atrial fibrillation (AF) has been largely debated. Aims: To describe the relationship between BMI categories and clinical outcomes in a large cohort of European AF patients. Methods: We included all AF patients with available baseline BMI and creatinine clearance and 1-year follow-up data enrolled in the EORP-AF General Long-Term Registry. Outcomes considered were: i) a composite of any thromboembolic event (TE)/acute coronary syndrome (ACS)/cardiovascular (CV) death; ii) CV death; iii) all-cause death. Results: A total of 7, 759 patients were included in this analysis. Of these, 55 (0.7%) were underweight, 2, 074 (26.7%) were normal weight, 3, 170 (40.9%) were overweight, 1, 703 (21.9%) were obese and 757 (9.8%) were severe obese. Mean age was progressively lower across the categories (p<0.0001), with proportion of patients aged≥75 years also progressively lower (52.7% in underweight to 19.4% in severe obese patients; p<0.001). Both underweight (41.8%) and severe obese (25.0%) patients were more likely symptomatic (p<0.001). Mean CHA2DS2-VASc score was higher in underweight patients (p=0.0325). Use of any oral anticoagulant therapy was progressively higher across the BMI categories (p<0.001). At 1-year follow-up the rate of all outcomes considered were highest for underweight patients and lowest in severe obese [Figure 1]. On univariate Cox regression analysis, being underweight was consistently associated to a higher risk for all outcomes, while increasing of weight categories was associated with progressively lower risk for adverse outcomes. After full adjustment with clinical and pharmacological characteristics, no effect of higher BMI classes was found for any outcome, but an independent association with an increased risk of CV death and all-cause death was seen for underweight patients (Table 1). Conclusions: In a large cohort of European AF patients a progressively lower rate of outcomes was found across increasing BMI classes. After full adjustments, no significant association was found between the higher BMI classes and outcomes. Underweight was associated with an increased risk for CV death and all-cause death. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Since the start of EORP programme, several companies have supported it with unrestricted grants